The moderating effect of reward satisfaction between job overload and emotional labor among nurses in small and medium-sized hospitals - Jun, Sooyoung (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigated how reward satisfaction moderates the relationship between job overload and emotional labor among nurses working in small and medium-sized hospitals (SMHs). A descriptive survey was conducted among 218 nurses from five SMHs. Data were collected using validated Korean versions of scales measuring job overload, emotional labor, and reward satisfaction. Hierarchical regression analysis was performed to examine the moderating effect of reward satisfaction on the relationship between job overload and emotional labor. Control variables included demographic factors such as age, gender, marital status, and clinical experience. Job overload was found to have a significant direct effect on emotional labor (β=0.48, p<.001). Additionally, the interaction between job overload and reward satisfaction significantly influenced emotional labor (β=0.24, p<.01). Reward satisfaction was identified as a key moderator in the relationship between job overload and emotional labor. Enhancing reward satisfaction may play a critical role in reducing the emotional burden caused by job overload. These findings suggest that interventions aimed at improving reward satisfaction could help alleviate the negative impact of job overload on emotional labor among nurses in SMHs.